2018
DOI: 10.1111/evo.13411
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of egg retention and fertilization success inDrosophila: One step closer to understanding the transition from facultative to obligate viviparity

Abstract: Oviparous, facultative egg retention enables Drosophila females to withhold fertilized eggs in their reproductive tracts until circumstances favor oviposition. The propensity to retain fertilized eggs varies greatly between species, and is correlated with other reproductive traits, such as egg size and ovariole number. While previous studies have described the phenomenon, no study to date has characterized within-species variation or the genetic basis of the trait. Here, we develop a novel microscope-based met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 144 publications
(312 reference statements)
6
21
1
Order By: Relevance
“…In extreme cases of strong constitutive egg retention, C. elegans strains exhibit partial viviparity, associated with significantly reduced maternal reproduction and survival. Overall, observed genetically variable duration of intra-uterine development in C. elegans thus seems to align well with past reports showing that transitions towards viviparity incur maternal fitness costs as observed for diverse invertebrate and vertebrate taxa with both inter- and intraspecific differences in parity modes (Avise, 2013; Blackburn, 2015; Horváth and Kalinka, 2018; Kalinka, 2015; Ostrovsky et al, 2015; Whittington et al, 2022). To what extent this apparent intergenerational fitness trade-off in C. elegans could involve shaped by parent-offspring conflict (Trivers, 1974) is uncertain.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In extreme cases of strong constitutive egg retention, C. elegans strains exhibit partial viviparity, associated with significantly reduced maternal reproduction and survival. Overall, observed genetically variable duration of intra-uterine development in C. elegans thus seems to align well with past reports showing that transitions towards viviparity incur maternal fitness costs as observed for diverse invertebrate and vertebrate taxa with both inter- and intraspecific differences in parity modes (Avise, 2013; Blackburn, 2015; Horváth and Kalinka, 2018; Kalinka, 2015; Ostrovsky et al, 2015; Whittington et al, 2022). To what extent this apparent intergenerational fitness trade-off in C. elegans could involve shaped by parent-offspring conflict (Trivers, 1974) is uncertain.…”
Section: Resultssupporting
confidence: 89%
“…The study of evolutionary transitions between ovi- and viviparity has concentrated on comparisons between species with distinct parity modes, so that evidence is mainly correlative and the genetic changes underlying such transitions can only rarely be determined (Horváth and Kalinka, 2018; Recknagel et al, 2021). Relatively few studies have examined quantitative intraspecific variation in egg retention although this approach may facilitate disentangling its relative costs and benefits.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting effect may be seen in both the laboratory and field oviposition trials as a reduction in oviposition as females are focusing on their own survival rather than egg laying. As eggs are immobile and unable to escape high temperatures, the reduction in reproductive oviposition in August could also be due to the females not depositing eggs in unfavourable environmental conditions and retaining eggs until conditions become optimum [ 40 , 41 ]. Such retention of eggs by D .…”
Section: Discussionmentioning
confidence: 99%
“…As it was observed before (Voigt and Kost 2021), this was more pronounced in females than in males. In response to unfavorable conditions, females sometimes, however, retain their mated eggs (Horváth and Kalinka 2018). Since many PcG targets function in development, and developmental time also varies with temperature (Trotta et al 2006), the observed patterns of temperature-dependent expression could also arise due to females retaining their eggs.…”
Section: Resultsmentioning
confidence: 99%